BIOTRANSFORMATION AND BIOLOGICALLY ACTIVE METABOLITES OF (R)-(-)-PHELLANDRENE - Iscan, G.; Kirimer, N.; Demirci, F.; Baser, K. HÃ¼snÃ¼ C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Biotransformation derivatives of natural and aromatic compounds may constitute an important resource for pharmaceutical, fragrance and aroma substances. From this point of view, in the present work, the monoterpene phellandrene was biotransformed by 16 different bacteria, fungi and yeasts. The metabolites of (R)-(-)-phellandrene were 6-hydroxypiperitone, phellandrene epoxide, cis-p-menth-2-en-1-ol, p-mentha-1(7),5-dien-2-ol (syn. yabunikkeol), 5-p-menthen-1,2-diol and carvotanacetone, which were characterized by GC-MS, 1D and 2D NMR techniques after chromatographic purifications. Furthermore, one of the major metabolites which is 5-p-menthen-1,2-diol was subjected to in vitro antibacterial, anticandidal by agar diffusion and microdilution and to TLC bioautographic bioluminescent Vibrio fischeri acute toxicity tests. The metabolite showed good inhibitory effects against various pathogenic bacteria (MIC 0.5-0.125 mg/ml) and Candida species (MIC 1-0.125 mg/ml) with relatively non-toxic (<10 mg/ml) properties detected by the V. fischeri bioluminescence assay. Acknowledgements: This research work is part of the PhD study of GI. Special thanks are addressed to Prof. Dr. R. G. Berger and Prof. Dr. W.-R. Abraham for providing some of the microorganisms employed in the biotransformation and bioassay studies. Infrastructures of TBAG 107T117 and BAP 060301 projects were used.